Surgical Treatment of Synovial Cyst in Scapholunate Joint - Diego Clemente Moreno; Juan Jesús Ortega Landeros; Lizbeth Paloma Herrera Alarcón, Miguel De Hoyos Riebeling; Iván San Pedro Rodríguez; Bárbara Alejandra Niño Robles; Alejandro Morales Rubio; Brenda Teresa López Mendoza; Mariana Maya Mulhia; Sergio Domínguez Mercado; Victor Manuel Pereyra Alba; Jairo Guadalupe Sifuentes Cortez; et al. (International Journal of Medical Science and Clinical Research Studies, 2024)
Ganglion cysts are the most common soft-tissue mass in the hand and wrist, making up 50% to 70% of all masses. They are most common in individuals in their twenties and forties, with women being affected three times more than males. The primary symptoms reported by people with wrist ganglion cysts are pain, weakness, and a visually unappealing look. Approximately 10% of patients report a prior traumatic experience being linked to the emergence of a ganglion cyst. Surgical treatment is often performed on an outpatient basis, using general anesthesia or axillary block anesthesia. A pneumatic tourniquet ensures a field without blood. Using a magnifying loupe is recommended to avoid detecting the pedicle and its connection to the ligaments below. Dorsal ganglion cysts involve making a transverse incision immediately above the cyst, dislodging the primary cyst from surrounding tissues using tenotomy scissors. Angelides’ approach involves making a curved cut through the capsule next to the cyst, allowing for the removal of capsular attachments and mucin ducts. To alleviate severe pain caused by dorsal ganglion cysts, it is recommended to surgically remove the posterior interosseous nerve above the extensor retinaculum. Volar wrist ganglion cysts involve making an incision along the radial side of the cyst, enabling both proximal and distal extension to reach distant capsular attachments. The ganglion is released from all adjacent connective tissue, and the radial artery is moved both towards the body and away from it. Precise control of bleeding is achieved using bipolar electrocautery, and the wound is thoroughly flushed with fluid. Skin margins are infused with a prolonged-acting local anesthetic, and the wound is sealed with intermittent 4-0 or 5-0 nylon sutures. Prompt mobilization is recommended, but a splint is not used until significant dissection has occurred.